Strategi Pembelajaran Berbasis Multiple Intelligences - Ach Syaikhu (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Education is one indicator that creates civilized humans. Every human being has basic intelligence that is owned. Where the basic intelligence describes the essence of self or self-wholeness. Without one of these intelligences, a person cannot become a complete and integrated person. Those basic intelligence are: IQ (Intellectual Intelligence), SQ (Spiritual Intelligence), EQ (Emotional Intelligence), and PQ (Physique Intelligence). The learning process is very important as seen by the role of teacher. When the learning process takes place, there is a process of teaching and learning. But this process is not necessarily going well. As for some of the goals that the author wants to achieve in this paper, among others are: 1) To find out what multiple intelligences are 2) To find out a learning strategy based on multiple intelligences. 3) To find out the teaching strategy for multiple intelligences. From this paper, the author hopes that educators will truly be able to master the multiple intelligences that exist in their students. For this reason, teachers must use Multiple Intelligences Research (MIR) to determine the tendency of students' intelligence. Pendidikan merupakan salah satu indikator keberhasilan menciptakan manusia yang beradab. Setiap manusia memiliki kecerdasan dasar yang pasti dimiliki. Dimana kecerdasan dasar tersebut menggambarkan hakikat diri atau keutuhan diri. Tanpa salah satunya seseorang tidak dapat menjadi pribadi yang utuh dan terintegrasi. Kecerdasan dasar tersebut yaitu kecerdasan IQ (Intellectual Intelligence), SQ (Spiritual Intelligence), EQ (Emotional Intelligence), dan PQ (Physique Intelligence). Proses pembelajaran sangat penting yang dipengaruhi peran guru didalamnya. Ketika proses pembelajaran berlangsung ada proses guru mengajar dan siswa belajar. Tetapi belum tentu proses ini berjalan dengan baik. Adapun beberapa tujuan yang ingin penulis capai dalam tulisan ini, antara lain 1) Untuk mengetahui apa itu kecerdasan jamak (multiple intelligences) 2) Untuk mengetahui strategi pembelajaran berbasismultiple intelligences. 3) Untuk mengetahui strategi mengajar multiple intelligences. Dari tulisan ini, Penulis memiliki harapan untuk para pendidik agar benar-benar mampu menguasai kecerdasan jamak yang ada pada peserta didiknya. Untuk itu, guru harus menggunakan Multiple Intelligences Research (MIR) guna mengetahui kecenderungan kecerdasan peserta didik.